CUSTOMER RELATIONSHIP MANAGEMENT APPLICATION SERVICES (CRM) FOR STUDENT ACTIVITY INFORMATION ON UNIVERSITIES (Case study : IBI DARMAJAYA) - Sri Karnila; Muhamad Galih Ramaputra; RZ Abdul Aziz (Proceeding International Conference on Information Technology and Business, 2017)
Information services application for students, is one of the form of loyalty from Universities to the students to be active and not left behind in existing information. Student information services previously informed through wall magazine, banner or brochures, this has not been delivered properly and didn't have any activities data either extracurricular activities or intracurricular activities. Regarding to all interested parties in IBI Darmajaya especially give best service to the student hence the importance of a Customer Relationship Management (CRM) Application to increase the flow of information needed by students, increasing student interest in every activity, having a database of the most interested activities and to accommodate IBI Darmajaya's interest. The data used in this research is all the activities information in the student affair, processed through Rational Unified Process (RUP) method with four phases done in sequence and iterative where each iteration can be used to fix iteration with visual programming language, hence resulting a well produced CRM application for information services. Keywords : CRM Application, Information, and SDLC.